Risk assessment in the federal government : managing the process (National Academy Press, 1983)
The regulation of potentially hazardous substances has become a controversial issue. This volume evaluates efforts to develop and use risk assessment guidelines, reviews the experience of regulatory agencies with different administrative arrangements for risk assessment, and evaluates various proposals to modify procedures.
Keywords: Cancer -- United States -- Prevention -- Decision making.; Health planning -- United States -- Decision making.; Health risk assessment.; Environmentally induced diseases -- United States -- Prevention.; Threshold limit values (Industrial toxicology); Probabilities.; Risk.; Environmental Exposure; Environmental Pollutants -- adverse effects; Government Agencies; Maximum Allowable Concentration; Probability; Risk; Health Status Indicators; United States; Decision making.; Health hazards.; Risk assessment.; Environmental factors.; Cancer -- États-Unis -- Prévention -- Prise de décision.; Santé publique -- Planification -- États-Unis -- Prise de décision.; Risques pour la santé -- Évaluation.; Exposition (Toxicologie); Limites d'exposition professionnelle (Toxicologie); Probabilités.; Risque.; probability.; POLITICAL SCIENCE -- Public Affairs & Administration.; Analyse des risques.; Commissions de contrôle.; Etats-Unis d'Amérique.; Santé publique.; Probabilities; Cancer -- Prevention -- Decision making; Environmentally induced diseases -- Prevention; Health planning -- Decision making; Health risk assessment; Kanker.; Gezondheid.; Risicoanalyse.; Overheidsbeleid.; Verenigde Staten.